Analisa Perbandingan Algoritma Prefix Code Dengan Algoritma Run Length Encoding Dalam Kompresi File Video - Meli Rahmawati; Nelly Astuti Hasibuan; Ilhamsah Ilhamsah (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
As the development of the world of technology is increasingly sophisticated and widespread in obtaining information quickly. Various kinds of technological facilities continue to be developed so that every human being can exchange information properly, especially in sending data such as video files, but large video files can cause problems in storage space and slow down when they want to send video file data. Therefore, a solution is needed to save storage media space and reduce the size of the data stored, reduce memory usage and file size without affecting the information in the file can be overcome by compression. Video compression is a data compression process that is carried out on video files with the aim of reducing video files so that they can be stored or sent quickly and efficiently. In the comparison of the two Prefix Code algorithms with the Run Length Encoding algorithm, both have a lossless compression algorithm, which is a type of compression that can be decompressed and after testing, the results obtained from the comparison of the two algorithms, that the Prefix Code algorithm is better than the Run Length Encoding algorithm. based on the bit size of the file after compression